LOWER TO MIDDLE MIOCENE MOLLUSC ASSEMBLAGES FROM THE TORINO HILLS (NW ITALY): SYNTHESIS OF NEW DATA AND CHRONOSTRATIGRAPHICAL ARRANGEMENT (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
The goal of this study is to correlate in chronostratigraphic order the fossil assemblages of selected, historical Lower and Middle Miocene localities of the Torino Hills. More than 18,000 specimens have been classified and assigned to 798 taxa (cf. Tab. I). The compositional analyses mainly concern the 672 listed gastropods, most of which were already described in classical monographies. The critical evaluation of the morphological and architectural shell parameters let to a significant reduction of the species that could be realistically maintained in comparison to those cited in literature from the Torino Hills Miocene. Six localities have been analyzed: Valle Ceppi (VC) and Val Sanfrà (VS) referred to the middle part of the Burdigalian stage (N7a Biozone), Villa Bertini at the topmost Burdigalian, Villa Allason (VA) and Villa Forzano (VF) at the early Langhian (N8 Biozone) and Monte dei Cappuccini (MC) at the late Langhian (N9 Biozone). On the whole, the fossil assemblages show a taxonomic variation of both biochronologic and palaeobiogeographic meaning. Actually, the similarity in specific biodiversity of VC, VS, VB, VA and VS reflects homogeneity among late Burdigalian to early Langhian palaeocommunities. As to MC, its deep difference on VC is correlatable with the eastern closing between the Mediterranean areas and the Tethyan Realm, at the boundary Burdigalian-Langhian, that brought to disjoint evolutions of the Mediterranean and Indo-Pacific palaeocommunities, the former being influenced by oceanic current changes and related climatic variations.
Keywords: Torino Hills; Molluscs; Gastropoda; Burdigalian; Langhian; Mediterranean; Paratethys; Aquitanian Basin